HEAT TRANSFER BETWEEN AN AUTOMOTIVE EXHAUST AND THERMOELECTRIC MODULES - Silva, A. L. C. (Revista de Engenharia Térmica, 2018)
This work aimed to study the heat transfer between an exhaust pipe of a car and thermoelectric modules. Heat transfer is the energy transport that occurs when quantities of matter that have different temperatures are placed in thermal contact and can occur in 3 different modes: conduction, convection and radiation. Thermoelectrics can convert thermal energy into electrical energy and vice versa. In this work a decision was made to install the Peltier cells in the final part of the exhaust pipe, where the temperature is lower. The temperature difference was 59°C. After calculations were found the values of the heat transfer rate: by conduction 0.164 W, by convection 0.103 and radiation 0.459.